Development potentials and their spatial patterns in Turkey - Toepfer, Helmuth (ERDKUNDE, 2005)
The analysis of six structural characteristics and their indicators demonstrate that in each case these indicators represent different socio-economic development potentials. The sum of these development potentials is presented in a summarising map (Fig. 7) and result in an overall picture of possible regionally differentiated development dynamics. To this end, the rank positions that the provinces obtained for the individual indicators were added and the sum totals were then divided into five classes by means of a cluster analysis. There is an additional figure 8 that enables to compare the situation of today with that of 1980-1985. Even though one can still generally speak of a west-east contrast regarding the potentials for possible further development, the differentiations within this overall picture show which development impulses are active in which areas. - The highest development potentials can still be found in the metropolises that have existed for a long time on account of their inherent self-strengthening process (see also WEDEL 1999). Therefore one has to assume that the west-east divide of development will continue to result in increasing divergences in future as well. - It also turned out that the expectation that a circle of highest potential development dynamics will arise (see TOEPFER 1989, 219) very quickly proved true. The spread effects starting from the metropolitan regions of Istanbul, Ankara, Izmir and Adana obviously do not act in all directions, rather primarily on the connecting axes between these regions. - The tourism on the south coast that, though marked by some setbacks, is still expanding, together with the rapid intensification of agriculture there (see STRUCK 1990) resulted in a strong economic diversification that developed a bridge of high development potentials between Adana and Izmir. - Towards the east, the northern provinces of Samsun and Amasya and the central eastern Anatolian provinces of Erzincan and Tunceli form possible starting points for regionally concentrated development chances that form a distinct contrast to the surroundings. - In the context of the Southeast Anatolia Project, the efforts to affect new development impulses by way of new irrigation systems and an intensification of agriculture already resulted in remarkable successes in the provinces of Gaziantep and especially Kilis (see STRUCK 1994, 2003). If the political condition remains stable, the situation could improve in the neighbouring provinces as well. Conclusion: Assuming a socio-economic development is made of the development of a series of different strands, it can be seen that single strands can at least partially lead both to convergences and to divergences. We will have to continue to observe which of these strands or structural characteristics will show themselves to be convergent or divergent in future.